DEVELOPMENT OF SUKUK IN THE STATE OF KUWAIT, ITS CHALLENGES AND PROSPECTS - Alowaiyesh, Waleed S. A. S.; Mohamad, Mohamad Taqiuddin; Mohd Noh, Mohd Shahid (Jurnal Syariah, 2020)
Ṣukūk emerged in the last two decades as a noteworthy contender for conventional bonds. Their wider appeal for Muslim populations around the world led to more issuers preferring to issuing ṣukūk over conventional bonds. This is the case for most countries in the Islamic World, but not Kuwait, despite it being a world-renowned pioneer and hub for innovation and creativity in Islamic Finance and Shariah-compliant capital markets. This study examines the legal and regulatory framework for ṣukūk in the State of Kuwait after giving a brief history of its development. Through qualitative analysis of news sources, country reports, and academic papers, this study attempts to identify the major challenges and hurdles facing the development of ṣukūk despite the illustrious track record of the Islamic Finance industry in Kuwait. As per the study, the most notable challenges and hurdles are in relation to the benchmark yield curve, public awareness, and listing of ṣukūk. The study concludes by suggesting possible solutions which all require a higher level of coordination between government entities and relevant stakeholders.